Evaluation of the Physiological Quality of Rice Seeds (Oryza sativa) under Salinity and Pyrite Stress Conditions - Hariy Laksamana; Alhaviz Alhaviz; Sri Utami Lestari (Journal of Applied Agricultural Science and Technology, 2025)
Salinity and pyrite are abiotic stress factors that can affect the physiological quality of rice seeds. This study aimed to evaluate the effects of salinity and pyrite stress on the viability and vigor of rice seeds. The research was conducted using a completely randomized design (CRD) with two factors: salinity levels (0 mM, 50 mM, and 100 mM NaCl) and pyrite dosages (0 mg, 200 mg, and 400 mg). The observed parameters included germination, maximum growth potential, vigor index, growth speed, simultaneous growth, and growth rate. The results showed that salinity stress significantly affected the vigor index and growth speed, while pyrite stress only influenced the growth speed. The interaction between the two factors did not show a significant effect on all physiological quality parameters of the seeds. However, there was a tendency for a decline in germination percentage, maximum growth potential, vigor index, growth speed, and simultaneous growth. The combination of high salinity stress (100 mM) and high pyrite dosage (400 mg) caused more pronounced growth retardation, particularly after day 10. Although rice seeds were able to maintain tolerance at low to moderate stress levels, an increase in the intensity of stress from both factors could hinder water and nutrient absorption, thereby reducing overall growth performance. The findings of this study provide insights into the tolerance limits of rice seeds to salinity and pyrite stress, which can serve as a basis for managing suboptimal lands for more sustainable rice production.